Arboviruses: variations on an ancient theme. (August 2014) - Jupille, Henri; Vega-Rua, Anubis; Rougeon, François; Failloux, Anna-Bella
ABSTRACT : Arboviruses utilize different strategies to complete their transmission cycle between vertebrate and invertebrate hosts. Most possess an RNA genome coupled with an RNA polymerase lacking proofreading activity and generate large populations of genetically distinct variants, permitting rapid adaptation to environmental changes. With mutation rates of between 10 - 6 and 10 -4 substitutions per nucleotide, arboviral genomes rapidly acquire mutations that can lead to viral emergence. Arboviruses can be described in seven families, four of which have medical importance: Togaviridae, Flaviviridae, Bunyaviridae and Reoviridae. The Togaviridae and Flaviviridae both have ssRNA genomes, while the Bunyaviridae and Reoviridae possess segmented RNA genomes. Recent epidemics caused by these arboviruses have been associated with specific mutations leading to enhanced host ranges, vector shifts and virulence.